2019
DOI: 10.4081/pr.2019.7997
|View full text |Cite
|
Sign up to set email alerts
|

Study of NT-pro-BNP and Hs-Troponin I Biomarkers for Early Detection of Children’s Heart Function of Protein-Energy Malnutrition

Abstract: The Protein Energy Malnutrition (PEM) is the condition of a lack of carbohydrate and protein stores in the body that trigger chronic failure nutrient intake and body maintenance function caused to impact the heart functions. The NT-pro-BNP and Hs- Troponin I proteins were found as the indicator of cardiac dysfunction. The sixty subjects of PEM, analyzed by standard of Indonesia Healt Ministry as well as nutritional status. The blood electrolytes examined by laboratory assay and the levels of Hs-Troponin 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Among these cardiac biomarkers, BNP has established role to recognize ventricular dysfunction irrespective of etiology 9 and cTn-I is considered as gold standard to detect myocardial injury irrespective of etiology. 10 In our study we mentioned that cardiac biomarker like cardiac troponin and BNP 11 would increase in children with SAM. We found that , out of 86 children with SAM, 32 (37.2%) children were increased BNP levels and 46 (53.5%) children had increased cTn-I levels.…”
mentioning
confidence: 71%
“…Among these cardiac biomarkers, BNP has established role to recognize ventricular dysfunction irrespective of etiology 9 and cTn-I is considered as gold standard to detect myocardial injury irrespective of etiology. 10 In our study we mentioned that cardiac biomarker like cardiac troponin and BNP 11 would increase in children with SAM. We found that , out of 86 children with SAM, 32 (37.2%) children were increased BNP levels and 46 (53.5%) children had increased cTn-I levels.…”
mentioning
confidence: 71%
“…19 The two important biomarkers known to reflect cardiac injury/cardiac dysfunction include NT-proBNP and hs troponin I. 13 B-type natriuretic peptide, a 32 amino acid polypeptide, contains a 17 amino acid ring structure with two cysteine residue connected by a disulfide bond.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] One of the earlier studies shows that the sensitivity and specificity of troponin can be used for the diagnosis of myocardial damage, whereas that of NT-proBNP can be used for diagnosis and to judge the effectiveness of cardiovascular therapy. 13 The release of NT-proBNP and troponin takes place by the cardiac myocytes in case of increased wall stress due to heart failure and myocardial dysfunction along with other natriuretic peptides. 13,28 Research has shown evidence of CVD to be common comorbidity in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations